2001
DOI: 10.1034/j.1600-0404.2001.103003175.x
|View full text |Cite
|
Sign up to set email alerts
|

S-100B and neuron-specific enolase in serum of mild traumatic brain injury patients
A comparison with healthy controls

Abstract: S-100B is a useful marker for brain damage in MTBI patients and seems to be associated with the presence of vomiting after the trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(85 citation statements)
references
References 15 publications
2
76
0
7
Order By: Relevance
“…This is likely due to the relatively small increase in serum NSE levels found as a result of MTBI. 101 One of the few other biomarkers that have been clinically tested in MTBI patients is tau. To test the diagnostic accuracy of C-tau in identifying MTBI patients with intracranial injuries, Kavalci et al 102 examined serum tau levels from 88 MTBI patients and correlated these changes with the presence or absence of intracranial lesions on their head CT. No significant difference in tau protein levels was detected between the two groups.…”
Section: Biomarkers For Mild Tbimentioning
confidence: 99%
“…This is likely due to the relatively small increase in serum NSE levels found as a result of MTBI. 101 One of the few other biomarkers that have been clinically tested in MTBI patients is tau. To test the diagnostic accuracy of C-tau in identifying MTBI patients with intracranial injuries, Kavalci et al 102 examined serum tau levels from 88 MTBI patients and correlated these changes with the presence or absence of intracranial lesions on their head CT. No significant difference in tau protein levels was detected between the two groups.…”
Section: Biomarkers For Mild Tbimentioning
confidence: 99%
“…Previous research has demonstrated that S-100β is superior to NSE in predicting the outcome status of both mild [20,21] and severe TBI subjects [22]. Wunderlich et al [23] showed that serum S-100β levels in acute stroke patients were predictive of neurological outcome at discharge and that serum NSE levels or lesion volumes obtained from CT scans did not add predictive value after adjusting for S-100β concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to an optimal S-100β cutoff of 39 pg/mL, 9 of 16 TBI subjects (56%) with baseline S-100β levels below this cutoff were back to normal daily activities within 2 weeks, as opposed to only 1 of 13 subjects (8%) with baseline S-100β levels above this cutoff (Fisher's exact P = 0.008). Subjects who did not return to normal activities after 2 weeks had a median NSE level of 13.8 ng/mL (interquartile range = [7,20]), whereas subjects who returned to normal activities after 2 weeks had a median NSE level of 6.4 ng/mL (interquartile range = [4.4, 12.2]); the difference was not statistically significant (P = 0.069). MBP (P = 0.183) could not discriminate between TBI subjects returning versus not returning to normal activities after 2 weeks.…”
Section: Correlation With Outcome Status After 2 Weeksmentioning
confidence: 93%
“…Discussion S100 protein is reported to be a sensitive and reliable marker of cellular brain damage. It can be applied for both primary diagnosis and long-term prognosis after severe TBI (27)(28)(29)(30)(31)(32). In the past, clinical studies predominantly used the Sangtec ᮋ 100 luminescence immunoassay, which is provided either for the LIAmat ᮋ S100 or the LIAISON ᮋ S100 analyzer (all from DiaSorin S.p.A., Dietzenbach, Germany).…”
Section: Roc Curve Analysis and Auc Calculation For S100 Serum Levelsmentioning
confidence: 99%